Solve the system of equations - 6x + 5y = 0 and -5x + 5y = -5 by combining
the equations.
|(-6x +5y = 0)
- 5х +5y
-5)
- 6x +5y
0
-5x +5y = -5
0 X+y=
try

Respuesta :

9514 1404 393

Answer:

  (x, y) = (-5, -6)

Step-by-step explanation:

The coefficients of y are the same, so we can eliminate y by subtracting one equation from the other. Here, we choose to subtract the first from the second, so that the coefficient of x ends up positive.

  (-5x +5y) -(-6x +5y) = (-5) -(0)

  x = -5 . . . . . . simplify

  -6(-5) +5y = 0 . . . . . . substitute x into the first equation

  6 +y = 0 . . . . . . . . . .  divide by 5

  y = -6 . . . . . . subtract 6

The solution to the system of equations is (x, y) = (-5, -6).